Práticas de aprendizagem em arte da performance – pesquisadocência -criação por uma intensionalidade inominável - Nardim, Thaise Luciane (Universidade Estadual de Campinas, 2018)
The thesis is constructed on encounters - and, triggered by them, on the compositions of vibrant bodies - between performance art, understood at first as a field and then as a set of forces; writing, taken as a set of forces opposed to compositions that privilege normative appropriateness as principles; education, understood in its specificity of being a practice, that is, a whole wherein the poetical and the political, thinking, doing and feeling can not be distinguished; and the practice of arts-based-research, whenre (sic) these intersections would become events. One practice is the machining field of the things of wich the thesis is an emerging form: the researcher-teacher-artist's processes of formation and un-formation as a teacher in charge of "teach" performance art in the context of an undergraduate course offered by a brazilian public university; Having as primary materials, narratives, quotations, descriptions, real and fictional characters, conversations on facebook and using procedures such as juxtapositions, floating attention dedicated to affections, content analysis, non-creative writing and deviations guided by attentive desire, the text could provide to the reader reading experiences with the practices it is.